Overweight Problem among Primary Health Care Workers in Suburban District of Hulu Langat, Selangor, Malaysia - Mustafa, Jamsiah; Salleh, Nazma Mohd; Isa, Zaleha Md.; Ghazi, Hasanain Faisal (Pakistan Journal of Nutrition, 2013)
Globally, overweight has become the epidemic due to world growth in industry, economy, urbanization and globalization. This study was conducted to highlight the overweight problem and its associated factors among health care workers in Suburban District of Hulu Langat, Selangor, Malaysia. A cross sectional study was conducted using IPAQ short version and Food Frequency Questionnaire to measure fat intake while knowledge was measured using a set of validated questionnaire. The anthropometric measurement was carried out using a calibrated SECA scale, body meter and measurement tape. Data was analyzed using software Diet 4. The overweight prevalence in this study is 46.1%. Age, sex, marital status, length of service, parity, education and income were significantly associated with overweight. However logistic regression showed that only education level and income has significant associations with overweight. It is concluded that the overweight prevalence among health workers is higher compared to previous studies in Malaysia. Higher income and low level of education are the predictors of overweight among health care workers.